Solitary Angiokeratoma of the Buccal Mucosa. Report of a Case - Andreadis Dimitrios; Poulopoulos Athanasios K.; Asimaki Anthi; Albanidou-Farmaki Eleni; Markopoulos Anastasios K. (Balkan Stomatological Society, 2014)
Background: Angiokeratoma is an asymptomatic, hyperkeratotic, capillary disorder of the skin present as solitary or multiple, keratotic papules or plaques, which may also be related to Fabry disease. Oral involvement may be observed in cases of widespread muco-cutaneous angiokeratomas, whereas solitary buccal angiokeratoma without systemic/cutaneous involvement is extremely rare.